Trends in Maternal Mortality in a Tertiary Care Hospital of Khyber Pakhtunkhwa - Maimoona Qadir (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Maternal mortality is an extremely devastating event for family, surviving children, hospital staff and community. Aim: To analyse the rate, demography, causes and timing of maternal deaths in a tertiary care hospital of Mardan. Methodology: This retrospective study was conducted in Gynaecology Department, Mardan Medical Complex, Mardan from January 2016 to December 2020. All patients received in the study period were included and counted and causative factors of maternal deaths were recorded. A predesigned proforma was used for collection of data from the medical records. SPSS 23.0 was employed for data analysis. Results: MMR of 657.7/100,000 live births was recorded. Most of the deaths (50%) were in 21-30 years age group, followed by 31-40 years age group (26%).34(39%) patients were multigravidas,27(31%) were primigravidas and 26(30%) were grand multigravidas.72(82.7%) were booked and 15(17%) were unbooked cases. Haemmorhage was responsible for 39(45%) maternal deaths, Hypertensive disorders ±HELLP caused 21(24%), Sepsis and thromboembolism caused 7(8%) each, cardiac diseases 5(5.7%), anesthesia complicated 3(3.4%), Anaphylaxis and hepatic encephalopathy lead to 2(2.2%) each, and epilepsy caused 1 maternal death. Most (44%) maternal deaths occurred in 6-12 hours of admission. Conclusion: The common causes of maternal mortality are haemmorhage, hypertensive disorders, sepsis and thromboembolism. Improvement of the maternity units in tertiary care facilitiesis need of the day and awareness of the general population is strongly favored to reduce or prevent maternal mortalities. Keywords: Maternal Mortality, Eclampsia, Postpartum Haemmorhage, Hypertension, Thromboembolism, Sepsis.